If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -6 = 24x + 1 Reorder the terms: -6 + 3x = 24x + 1 Reorder the terms: -6 + 3x = 1 + 24x Solving -6 + 3x = 1 + 24x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-24x' to each side of the equation. -6 + 3x + -24x = 1 + 24x + -24x Combine like terms: 3x + -24x = -21x -6 + -21x = 1 + 24x + -24x Combine like terms: 24x + -24x = 0 -6 + -21x = 1 + 0 -6 + -21x = 1 Add '6' to each side of the equation. -6 + 6 + -21x = 1 + 6 Combine like terms: -6 + 6 = 0 0 + -21x = 1 + 6 -21x = 1 + 6 Combine like terms: 1 + 6 = 7 -21x = 7 Divide each side by '-21'. x = -0.3333333333 Simplifying x = -0.3333333333
| (1x+135)+(1x+65)=180 | | -3sin^2(x)=3cos^2(x) | | 52=10n-8 | | 8.01x+56.07=112.14 | | 22x+5+14x-5=180 | | -7x+8=1-8x | | 3x-45+2=7 | | (y^2-9)*(y^2-9)*(y^2-9)=0 | | -15z+-40-5=-20 | | 6/7x-5/7=4 | | 50h+75=225 | | 36x^2+36y^2+144x-360y=-1019 | | 2(25-9)+6b=-7 | | (9^2)^1/3 | | -2x-hi=24+6i | | 1/6X^3=-36 | | -4(x-4)=24 | | 2/3x=80 | | Cos(3x)-(cosx)=0 | | -1/6m-5/8+3/4m=7/4 | | px(-p+6)=0 | | 7u/7 | | (2-u)(3u-1)=0 | | 6/7x-3/7=8 | | 9a+18c=0 | | -3(4b-10)=1/2(-24b=60) | | 8n-(2n+7)=7 | | 9u^6/81u^4 | | 9u^6/81u^4 | | 8n-(2n+7)=7 | | 5x+7x=-72 | | 8n-(2n+7)=7 |